Influence of pipeline steel surface on the thermal stability of methane hydrate - Wu, Guozhong; Tian, Linqing; Ha, Li; Feng, Feng; Yang, Zhifeng; Feng, Jing-Chun; Coulon, Frederic; Jiang, Yuelu; Zhang, Ruifeng (Elsevier, 2022)
The thermal stability and surface adhesion of natural gas hydrate are critical for the safety of oil and gas pipelines. The roughness and hydrophobicity of the pipe surface often vary during long-distance transportation, but it remains unclear about how these variances influence the hydrate stability. In this study, twelve molecular models of solid steel pipeline surfaces with random morphology were evaluated and molecular dynamics simulations were performed to gain insights into the kinetics of methane hydrate dissociation, the nucleation and growth of gas bubbles during hydrate decomposition, and the free energy of hydrate adhesion to the solid steel surface. Results demonstrated that the stability of methane hydrate could be decreased by up to 85% by increasing the hydrophobicity of the pipe surface by 52%. The bubble nucleation site of the gas released from hydrate decomposition shifted from bulk water to the solid surface by increasing the surface hydrophobicity (εsw: 3.73–5.74 kJ mol−1), but a highly hydrophobic surface (εsw: 2.73 kJ mol−1) made it hard to form gas bubble on either smooth or rough surface. Moreover, the free energy of hydrate adhesion also depended on the roughness and hydrophobicity of the solid surface, while the largest energy barrier for the adhesion of methane hydrate was found on the hydrophobic surface with high roughness. The findings from this study provided theoretical support for better understanding the methane hydrate evolution principles when the surface properties of the pipe wall changed from naturally occurred events (e.g., metal corrosion) or artificial treatment (e.g. chemical coating).
Keywords: methane hydrate; roughness; hydrophobicity; thermal stability; adhesion